STRATEGI KOMUNIKASI DINAS PARIWISATA DAN KEBUDAYAAN KOTA PARIAMAN DALAM MEMPROMOSIKAN TRADISI HOYAK TABUIK PIAMAN PASCA WABAH COVID-19 MELANDA DI INDONESIA - Heru Maulana (Jurnal Komunikasi, 2024)
Research in the background by increasing the number of tourist hoyak tabuik piaman 2022, namely during the period of covid-19 exactly at the extension of ppkm level-1. This is a comparison by researchers, namely in 2018, 2019 in this year, tabuik tourist are not as much as 2022. This increase became attraction for researchers in conducting a study and then figuring out what communication strategy were done by tourism and culture of Pariaman city in promoting this hoyak tabuik traditon so that there was an increase. The research methodology used by researchers is a qualitative descriptive in which researchers obtain data by interviews, documentation, and other data in the field. The result of this study show that communication strategies carried out by tourism and culture services of the city Pariaman in the promoting the tradition hoyak tabuik piaman post covid-19 struck in Indonesia have been succesfull, this can be proved by the increase of tourist with the foundation of data obtained by researchers in the field